Rectosigmoid sparing en bloc pelvic resection for fixed ovarian tumors: Surgical technique and perioperative and oncologic outcomes - Shan, Ying; Jin, Ying; Li, Yan; Gu, Yu; Wang, Wei; Pan, Lingya (Frontiers in Oncology, 2022)
Purpose: Patients with advanced ovarian cancer often undergo en bloc rectosigmoid resection with total hysterectomy to completely debulk the pelvis. We describe a unique rectosigmoid sparing en bloc pelvic resection technique for fixed ovarian tumors infiltrating the colon wall. Methods: From July 2020 to June 2021, 20 patients with advanced EOC underwent rectosigmoid sparing en bloc pelvic resection successfully at our institution. We summarized our surgical technique and the peri-operative and oncological outcomes. Results: Twenty cases with bowel infiltration achieved en bloc pelvic resection with rectosigmoid tumorectomy in a centripetal fashion. Only 2 patients required mucosal repair. None of the patients experienced any complications associated with en bloc resection. No pelvic recurrence occurred within the median follow-up time of 12 months. Conclusion: Rectosigmoid sparing en bloc pelvic resection may be feasible for select patients with fixed ovarian tumors infiltrating the colon wall.